2017
DOI: 10.1038/s41598-017-07927-w
|View full text |Cite
|
Sign up to set email alerts
|

Stability of volcanic ash aggregates and break-up processes

Abstract: Numerical modeling of ash plume dispersal is an important tool for forecasting and mitigating potential hazards from volcanic ash erupted during explosive volcanism. Recent tephra dispersal models have been expanded to account for dynamic ash aggregation processes. However, there are very few studies on rates of disaggregation during transport. It follows that current models regard ash aggregation as irrevocable and may therefore overestimate aggregation-enhanced sedimentation. In this experimental study, we u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
21
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 32 publications
(23 citation statements)
references
References 48 publications
1
21
0
Order By: Relevance
“…The influence of the different starting materials in the particle plume seems to be of subordinate importance. Volcanic field studies and experiments have shown that preservation of aggregates is critically depending on the availability of soluble salt compounds such as NaCl or CaSO 4 (Gilbert and Lane 1994 ; Mueller et al 2017b ). Volcanic eruptions offer two ways to precipitate salts on ash surfaces: (1) through precipitation of salt crystals (e.g., NaCl) out of salt rich brines (e.g., interaction of volcanic ejecta with sea water during phreatomagmatic eruptions) or (2) through diffusion-driven precipitation after the chemical interaction of acid solutions (e.g., HCl or H 2 SO 4 ) with ash particles (e.g., Ayris et al 2013 , 2014 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The influence of the different starting materials in the particle plume seems to be of subordinate importance. Volcanic field studies and experiments have shown that preservation of aggregates is critically depending on the availability of soluble salt compounds such as NaCl or CaSO 4 (Gilbert and Lane 1994 ; Mueller et al 2017b ). Volcanic eruptions offer two ways to precipitate salts on ash surfaces: (1) through precipitation of salt crystals (e.g., NaCl) out of salt rich brines (e.g., interaction of volcanic ejecta with sea water during phreatomagmatic eruptions) or (2) through diffusion-driven precipitation after the chemical interaction of acid solutions (e.g., HCl or H 2 SO 4 ) with ash particles (e.g., Ayris et al 2013 , 2014 ).…”
Section: Discussionmentioning
confidence: 99%
“…Volcanic eruptions offer two ways to precipitate salts on ash surfaces: (1) through precipitation of salt crystals (e.g., NaCl) out of salt rich brines (e.g., interaction of volcanic ejecta with sea water during phreatomagmatic eruptions) or (2) through diffusion-driven precipitation after the chemical interaction of acid solutions (e.g., HCl or H 2 SO 4 ) with ash particles (e.g., Ayris et al 2013 , 2014 ). Whereas the latter mechanism may also apply for impact events, salts for binding aggregates here may further depend on the chemistry of the target material and hence significantly influence aggregation efficiency: carbonite rich cherts as in the Ries area may significantly boost the generation/presence of such salts like gypsum or calcium chloride on ejecta particles, which will in turn improve aggregate stability and their chance of preservation (Mueller et al 2017b ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…One of the main goals of modern volcanology is a better understanding and quantification of eruption source parameters (ESP) governing tephra dispersal during a volcanic crisis. This is done using field (e.g., Andronico, Cristaldi, et al, ; Andronico, Scollo, et al, ; Andronico, Scollo, Lo Castro, et al, ), remote‐sensing retrievals (e.g., Corradini et al, , ; Gouhier et al, ; Scollo et al, , ), laboratory experiments (e.g., Bagheri & Bonadonna, ; Cigala et al, ; Mueller, Ayris, et al, ; Mueller, Kueppers, et al, ), and numerical models (e.g., Bonadonna & Costa, ; Folch et al, ; Scollo et al, ). ESP assessment (e.g., Folch, ; Mastin et al, ) involves the estimation, among others, of the mass eruption rate (MER), which combined with the eruption duration provides the total erupted mass (TEM).…”
Section: Introductionmentioning
confidence: 99%
“…U nderstanding the stability and strength of particle assemblies subject to disruptive forces is essential for predicting the macroscopic mechanical behavior of geological, biological, and industrial particulate materials (1)(2)(3). Hallmarks of such systems include size polydispersity and nonequilibrium dynamics (4,5).…”
mentioning
confidence: 99%